2004
DOI: 10.1046/j.1365-2036.2004.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of familial hepatocellular carcinoma caused by chronic hepatitis B infection in Hong Kong

Abstract: SUMMARYBackground: Hepatitis B virus infection is an important aetiological factor for hepatocellular carcinoma. Clusters of hepatocellular carcinoma have been observed in families infected with hepatitis B virus. Aim: To investigate the prevalence and characteristics of hepatocellular carcinoma associated with familial hepatitis B virus in Hong Kong. Methods: Hepatitis B virus patients were screened for familial hepatocellular carcinoma using a standardized questionnaire. The clinical features of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…Cirrhosis of the liver or HCC occurred earlier in the offspring. Similar results have been described for familial HCC in Hong Kong [Chan et al, ]. These results indicate that unfavorable prognoses (cirrhosis of the liver or HCC) in these families may be associated with genetic defects.…”
Section: Discussionsupporting
confidence: 87%
“…Cirrhosis of the liver or HCC occurred earlier in the offspring. Similar results have been described for familial HCC in Hong Kong [Chan et al, ]. These results indicate that unfavorable prognoses (cirrhosis of the liver or HCC) in these families may be associated with genetic defects.…”
Section: Discussionsupporting
confidence: 87%
“…The HBV carrier rate was 17.3% in our cohort, which is higher than in the general population in Hong Kong [31]. There is evidence that HBV infection is more common in patients with lymphoma [32,33].…”
Section: Hbv Reactivation In All Patients With Hbv Infectioncontrasting
confidence: 53%
“…16,3133 Turati et al 18 conducted a case-control study (229 HCC patients vs 431 controls) and showed that the odds ratio of HCC was significantly higher in patients who had a family history of HCC and viral hepatitis B or C. They did not find a multiplicative interaction in their study. However, they did not examine RERI, AP, and SI to assess interaction.…”
Section: Discussionmentioning
confidence: 99%